The Private Government of Public Money : Community and policy inside British politics - Heclo, Hugh.; Wildavsky, Aaron B. (London : Macmillan, 1974)
This book examines the expenditure process as it actually operates in British central government. It also uses the expenditure process as a spotlight for illuminating the characteristics practices of British central government.
Includes index.
Bibliography: p. [390]-392.
osc 15/06/17
Loans
Keywords: Government spending policy; Politics and government; Expenditures, Public; Political planning; Great Britain